Development of Synergistic, Dual Pd‐Cu@rGO Catalyst for Suzuki, Heck and Click Reactions: Facile Synthesis of Triazole or Tetrazole Containing Biaryls and Stilbenes. Issue 28 (26th July 2018) - Gupta, Ajay; Jamatia, Ramen; Dam, Binoyargha; Pal, Amarta K.
Abstract: A dual synergistic Pd−Cu@rGO catalyst was synthesized and characterized by various analytical techniques. From powder X‐ray diffraction, Raman, FT‐IR and X‐ray photoelectron spectroscopy analysis it was evident that graphite oxide was reduced during decoration with metal nanoparticles on its surface. The percentages of Cu and Pd in the catalyst was also evident from inductive coupled plasma‐atomic emission spectroscopy analysis. After the preparation and characterization of the catalyst, it was employed in Suzuki and Heck reactions. It was also established that the catalyst was efficient in tetrazole and triazoles synthesis (Click reaction). Further, the present catalyst was effective in furnishing the biaryls/stilbenes and tetrazoles/triazoles skeletons in the same organic compound via step wise reactions. The catalyst also showed good catalytic activity in gram scale reaction. The catalyst could be recycled and reused up to seven consecutive runs without not much loss in its catalytic activity. It was evident from TEM, SEM, EDX and FT‐IR analysis that the general morphology and characteristic of reused Pd−Cu@rGO remained almost unchanged. Abstract : A synergistic, dual Pd‐Cu@rGO catalyst was prepared and characterized using TEM, SEM, EDX, PXRD, XPS, FT‐IR, Raman, ICP‐AES and TGA analysis. The prepared synergistic catalyst efficiently drove Suzuki, Heck and Click reactions under benign conditions. Further, the present catalyst was applied for the facile synthesis of triazole or tetrazole containing biaryls and stilbenes. The reusability of the catalyst and excellent gram scale reaction are some of the sustainable, economic and industrially beneficial outcomes of the present protocol.